Effect of Aesthetic Images on a Population with Mild Cognitive Decline: An Electroencephalography/Functional Near-Infrared Spectroscopy Study - Livio Clemente; Marianna La Rocca; Marianna Delussi; Giusy Tancredi; Katia Ricci; Giuseppe Procida; Antonio Brunetti; Vitoantonio Bevilacqua; Marina de Tommaso (Proceedings)
Neuroaesthetics is a relatively young field that connects neuroscience with empirical aesthetics and originates in the neurological theory of aesthetic experience. It investigates brain structures and activity during the phenomena of artistic perception and production and, at the same time, attempts to understand the influence of neurological pathologies on these mechanisms. For each participant (six subjects with mild cognitive decline and ten controls), electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) data were acquired thanks to a wearable EEG–fNIRS system during the execution of a P300 task.